2022
DOI: 10.3389/fpubh.2022.914950
|View full text |Cite
|
Sign up to set email alerts
|

Will People Accept a Third Booster Dose of the COVID-19 Vaccine? A Cross-Sectional Study in China

Abstract: ObjectiveThe coronavirus disease 2019 (COVID-19) vaccines are considered to be an effective way to prevent the spread of the infection. Our previous study has shown that about 75% of healthcare workers (HCWs) in China were willing to receive the vaccine when it became available. Here, we examined the acceptance of a third booster dose among Chinese people and identified the influencing factors.MethodsA cross-sectional online survey was conducted and the snowball sampling method was utilized. An online question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…This is in line with our previous findings, which suggested that public education on the benefits of vaccines needs to be improved in order to increase vaccine uptake [39]. Another study also found people who believe that the COVID-19 vaccine is effective were 7.95 times more likely to receive a third or booster dose compared to those who do not [40]. Therefore, information on the effectiveness of the vaccine should be well-communicated through simple and effective techniques to community members so that they are well-informed.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with our previous findings, which suggested that public education on the benefits of vaccines needs to be improved in order to increase vaccine uptake [39]. Another study also found people who believe that the COVID-19 vaccine is effective were 7.95 times more likely to receive a third or booster dose compared to those who do not [40]. Therefore, information on the effectiveness of the vaccine should be well-communicated through simple and effective techniques to community members so that they are well-informed.…”
Section: Discussionsupporting
confidence: 91%
“…Vaccine-associated adverse events were the most frequently reported predictor of CBVH in 27 studies (64.29%). The main drivers for CBVH were fear about the side effects of booster vaccines [ 4 , 21 , 30 , 45 , 47 , 50 ], the severity of side effects associated with previous COVID-19 vaccines [ 26 , 29 , 31 , 34 ], concerns about adverse reactions to booster vaccines [ 6 , 52 ], adverse reactions experienced personally or among friends and family following previous COVID-19 vaccinations [ 5 , 7 , 30 , 52 ], and receipt of medical care following the COVID-19 vaccine primary doses [ 37 ]. Other studies reported uncertainty, risk, and safety concerns associated with booster doses [ 5 , 13 , 20 , 26 , 43 , 44 , 49 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Perceptions of the benefits and effectiveness of boosters were frequent determinants of CBVH. Greater CBVH rates were associated with a lack of confidence and trust in the effectiveness of the booster dose [ 2 , 4 , 8 , 30 , 31 , 47 , 51 ], concerns or uncertainty about the efficacy of COVID-19 vaccines [ 5 , 6 , 21 , 44 , 50 , 52 ], and low perceived benefits of boosters [ 34 , 43 , 49 ]. Similarly, high response efficacy (i.e., the belief that receiving a booster will prevent COVID-19) was significantly associated with lower hesitancy among Chinese adults [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…With this scale, we found that the COVID-19 vaccine booster hesitancy was 14.81% in Zhejiang Province during November to December 2021, which was roughly consistent with the national investigation in China (16.1%) conducted in late January 2022 with an online sample of 898 [ 37 ]. Other two domestic web-based national surveys [ 36 , 41 ] carried out during November–December 2021 with thousands of samples demonstrated much higher booster acceptance rate (90.39%, 93.5%), which may be due to the different geographical region and epidemic background. It is likely that the hesitance will largely decline as China has started to ease COVID-19 restrictions since December 2022 due to decreasing pathogenicity of the Omicron variant, which may promote booster acceptance to cope with step-by-step reopening policy.…”
Section: Discussionmentioning
confidence: 99%
“…It is urgent for policymakers to explore the obstructions and underlying concerns of the booster, so as to encourage timely interventions to promote acceptance. Although previous studies [ 23 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] conducted similar surveys on booster hesitancy, the influential factors varied with different policy background, COVID-19 prevalence and predominant variants, COVID-19 vaccine type and supply capacity, public awareness of vaccine literacy and non-pharmaceutical interventions (NPIs), as well as investigation periods and religious beliefs.…”
Section: Introductionmentioning
confidence: 99%